HPTLC FINGER PRINTING METHOD FOR THE DETERMINATION OF AMINO ACIDS FROM ETHANOLIC EXTRACT OF PALMYRA PALM FRUIT PULP(Borossus flabellifer) - B.VIJAYAKUMARI; P.C.VENGAIAH; P.KIRANMAYI (International Journal of Pharma and Bio Sciences, 2015)
To identify the presence of various amino acids in ethanolic extract of palmyra fruit pulp, HPTLC finger printing analysis was carried out. The analysis was carried out by using CAMAG LINOMAT5 instrument which revealed the presence of five amino acids especially alanine, valine, methionine, leucine and phenylalanine with Rf values 0.16, 0.21, 0.27, 0.35, 0.37. The concentration of phenylalanine was maximum (36.56 mg/100mg) and methionine was present in minimum concentration (1.49 mg/100 gm).